Utilização da energia fotovoltaica na alimentação do sistema de climatização de aviários - Menegotto, Lucas Ramos (2018)
This paper presents a technical-economic study on the installation of a photovoltaic generator connected to the power grid in a rural property with poultry farming located in Viadutos municipality, in Rio Grande do Sul state. Initially, a bibliography review is made to understand the system operation, from the photovoltaic cell to the connection with the power grid, taking into account the rules established by ANEEL. After that, the methods that will be used in the course of the generator sizing work are presented, considering the climatic conditions of the chosen location, the demand to be served and the available roof area. It also shows the methodology for the economic analysis of the photovoltaic system, considering mainly the energy to be generated by the system and the energy price paid to the concessionaire. Budgets are presented with three different companies in the industry for a price comparison. The results show the economic analysis of the investment with a twenty-five year horizon and the comparison with other investments.